(untitled) (Revista Brasileira Multidisciplinar, 2008)
The article intends to show the establishment of the aircraft industry in the Central Administrative Region (SP), in the last seven years, which introduced a new element in the economical structure of the region. Based on the innovation systemic approach , the objective is to identify and characterize the investments related to the aircraft industry segment carried out in the region and to identify the potentialities of the new production geographical axle and aircraft’s maintenance for a dynamic setorial insertion, given by the capacity of integration to innovation system related to the aircraft industry. Some qualitative information was obtained from primary (questionnaires) and secondary sources. For the analysis, all the information was organized taking into consideration the most important aspects of the innovation activities according to the Oslo Manual. Technology and efficient staff are the strategic factors to this type of industry. Based on these requirements, they have potentialities in the Central Administrative Region (CAR) for a possible insertion in the innovation system: (i) the favorable institutional environment concerning the education system, availability and training of human qualified resources, which demonstrated fast structuring capacity seeking to attend a new demand that appeared in the region; (ii) Technology & Science infrastructure.